2021
DOI: 10.1080/2331186x.2021.1892943
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of experience in L2 teachers’ turnover intentions/occupational stress and psychological well-being/grit: A mixed methods study

Abstract: The present mixed methods study examined the relationships among Iranian English as a Foreign Language (EFL) teachers' turnover intentions, occupational stress, psychological well-being, and grit in light of their teaching experience. The participants of the study were a total of 325 EFL teachers (138 novice and 187 experienced). To collect the data, four instruments of occupational stress, turnover intentions, grit, and well-being were administered to the participants, followed by semi-structured interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 51 publications
(54 reference statements)
1
24
0
Order By: Relevance
“…However, demographic moderators such as age [84] and experience Staniland, et al [85] influence employee turnover. Another study also found the effect of teacher experience on turnover due to psychological stress [86]. Therefore, this study has also included age and experience as moderators of turnover intention.…”
Section: Demographics and Turnover Intentionmentioning
confidence: 98%
“…However, demographic moderators such as age [84] and experience Staniland, et al [85] influence employee turnover. Another study also found the effect of teacher experience on turnover due to psychological stress [86]. Therefore, this study has also included age and experience as moderators of turnover intention.…”
Section: Demographics and Turnover Intentionmentioning
confidence: 98%
“…They also maintained that the improvement of grittiness among learners through increasing their persistence, flexibility, and steadiness can develop their psychological well-being. Nazari and Alizadeh Oghyanous ( 2021 ) investigated relationships among novice and experienced teachers' psychological well-being, job-related pressure, and grit in EFL contexts. Their study found out that correlations among EFL teachers' job-related pressure, well-being, and grittiness are higher and significant among novice teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beyond the university setting, Rangarajan et al (2020) found grit lessens the effect of life event personal stress on depersonalization among B-to-B salespeople. Nazari and Oghyanous (2021) found a negative correlation between grit and occupational stress among novice instructors teaching English in Iran. Although these studies did not specifically examine job stress, they do suggest a negative relationship exists between grit and job stress.…”
Section: Grit and Job Stressmentioning
confidence: 87%